IMPLEMENTASI AKUNTANSI PADA PONDOK PESANTREN YAYASAN AGUNG NUR MUHAMMAD - Risqika Yunafiroh; Novi Tri Oktavia; Antri Arta (Jurnal PROFITA : Akuntansi dan Manajemen, 2022)
This istudy iaims ito iexamine ithe iextent iof ithe iapplication iof iaccounting ithat iapplies ito ithe iislamic iboarding ischool iof ithe iAgung iNur iMuhammad iFoundation iwith iapplicable iaccounting istandards. This iresearch iuses iqualitative iresearch imethods, iusing isecondary idata. Accounting ifor iislamic iboarding ischools iis ia iprocedure ifor ipreparing ifinancial istatements ito iproduce ifinancial iinformation iby iconsidering ithe icharacteristics iand iinternal iproperties iof iislamic iboarding ischools. The ifindings iin ithis istudy ireveal ithat ithe iaccounting icontained iin ithe iislamic iboarding ischool iof ithe iAgung iNur iMuhammad iFoundation ihas iapplied iaccounting ieven ithough iit iis inot icompletely iperfect. The ineed ito iimprove iaccounting ito icomply iwith iapplicable istandards iby ilearning iand iimproving ithe irecords ithat ihave ibeen iapplied ito ithe iislamic iboarding ischool iof ithe iAgung iNur iMuhammad iFoundation.